Meter Running Speed of University Students: Basketball Dribbling Ability - Suwardi, Suwardi (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This study aims to analyze the effect of 30-meter running ability on the basketball dribbling ability of students of the Sports Coaching Education Study Program, UPRI Makassar. The research method uses a quantitative approach with a correlational design. The research sample consisted of 22 PKO UPRI Makassar students. We collected data using a 30-meter running speed test and a basketball dribbling ability test. Data analysis used a linearity test and regression test. The results showed an R-squared value of 0.014, meaning that 30-meter running speed for basketball dribbling ability was not significant. We conclude that the basketball dribbling ability of PKO UPRI Makassar students remains unaffected by a significant value of 0.605, which is greater than 0.05. The conclusion is that there is no significant effect between 30-meter running ability and basketball dribbling ability among PKO UPRI Makassar students. This finding is contrary to several previous studies that stated a close relationship between running speed and basketball dribbling skills.